1994
DOI: 10.1017/s0022149x00014395
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific development of a filarial nematode (Dipetalonema dracunculoides) in vector ticks

Abstract: This paper reports the development of the canid filarial worm, Dipetalonema dracunculoides, in the brown dog tick, Rhipicephalus sanguineus by determining whether development is similar within larval, nymphal and adult stages of infected ticks. This study demonstrates that only infected nymphal ticks can support the complete development of the filarial worm. Infected larval ticks are not suitable intermediate hosts, nor are infected adults. Development depends on some stage-specific property of the vector, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Although the presence of A. dracunculoides in central and eastern Europe has not yet been reported despite systematic surveillance in both domestic and wild carnivores (Ionicȃ et al, 2015(Ionicȃ et al, , 2016(Ionicȃ et al, , 2017a(Ionicȃ et al, , 2017b, the presence of its vectors should raise awareness. However, the louse flies (Hippoboscidae) are not the sole vectors of this parasite as ticks [Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae)] have also been incriminated (Olmeda-Garcia et al, 1993;Olmeda-Garcia & Rodriguez-Rodriguez, 1994;Mihalca et al, 2012;Dantas-Torres & Otranto, 2015). Hence, the importance of this finding, together with the underlying factors determining the distribution of H. longipennis, require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of A. dracunculoides in central and eastern Europe has not yet been reported despite systematic surveillance in both domestic and wild carnivores (Ionicȃ et al, 2015(Ionicȃ et al, , 2016(Ionicȃ et al, , 2017a(Ionicȃ et al, , 2017b, the presence of its vectors should raise awareness. However, the louse flies (Hippoboscidae) are not the sole vectors of this parasite as ticks [Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae)] have also been incriminated (Olmeda-Garcia et al, 1993;Olmeda-Garcia & Rodriguez-Rodriguez, 1994;Mihalca et al, 2012;Dantas-Torres & Otranto, 2015). Hence, the importance of this finding, together with the underlying factors determining the distribution of H. longipennis, require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Hafez and Hilali [26] however demonstrated that the fly could only withstand starvation for 12 to 36 hours before dying and that feeding occurs more regularly than this. It is reported that the developmental period from L1 to infective larvae for A. reconditum in fleas and A. dracunculoides in ticks is approximately seven days and thirteen days, respectively [16,27]. The development of Acanthocheilonema sp.?…”
Section: Discussionmentioning
confidence: 99%
“…Fleas and lice are intermediate hosts for A. reconditum [14]. Ticks, lice [15,16] and, in Algeria, H. longipennis , have all been proposed as intermediate hosts for Acanthocheilonema dracunculoides [17]. The development of larvae in these intermediate hosts occurs mostly in the fat-body cells and infective larvae migrate to the mouthparts to facilitate their transmission [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The brown dog tick (Rhipicephalus sanguineus) is well known as a vector of some pathogens of dogs such as Babesia canis [7,16], Babesia gibsoni [7,16], Hepatozoon canis [2], Ehrlichia canis [10], Coxiella burnetii [8], spotted fever group rickettsia [1], and the filaria nematode Dipetalonema spp [12,13]. However, there have been few reports on the distribution of R. sanguineus except in Okinawa Prefecture in Japan [18].…”
mentioning
confidence: 99%
“…As the detail structure could not be observed in the smear, the species of the microfilaria was not identified. Rhipicephalus sanguineus is a vector of dog filaria, D. dracunculoides [12,13]. The microfilaria might have belonged to Dipetalonema spp.…”
mentioning
confidence: 99%